Regional‐scale controls on dissolved nitrous oxide in the Upper Mississippi River. Issue 9 (6th May 2016) - Turner, P. A.; Griffis, T. J.; Baker, J. M.; Lee, X.; Crawford, J. T.; Loken, L. C.; Venterea, R. T.
Abstract: The U.S. Corn Belt is one of the most intensive agricultural regions of the world and is drained by the Upper Mississippi River (UMR), which forms one of the largest drainage basins in the U.S. While the effects of agricultural nitrate (NO3 − ) on water quality in the UMR have been well documented, its impact on the production of nitrous oxide (N2 O) has not been reported. Using a novel equilibration technique, we present the largest data set of freshwater dissolved N2 O concentrations (0.7 to 6 times saturation) and examine the controls on its variability over a 350 km reach of the UMR. Driven by a supersaturated water column, the UMR was an important atmospheric N2 O source (+68 mg N2 O N m −2  yr −1 ) that varies nonlinearly with the NO3 − concentration. Our analyses indicated that a projected doubling of the NO3 − concentration by 2050 would cause dissolved N2 O concentrations and emissions to increase by about 40%. Key Points: The Mississippi River is an important N2 O source throughout the ice‐free period The N2 O:NO3 − mass ratio is nonlinear, implying an upper bound on N2 O concentrations A doubling of riverine NO3 − would increase N2 O emissions by about 40%